Acquired immune deficiency syndrome-related intravascular large B-cell lymphoma primarily arising from lymph nodes: a case report - Zhang, Wei; Li, Qi sui; Deng, Chang Gang; Yuan, Jing (Frontiers in Oncology, 2026)
BackgroundIntravascular large B-cell lymphoma (IVLBCL) is a rare subtype of diffuse large B-cell lymphoma, with nodal involvement being particularly uncommon. Due to its atypical clinical presentation, timely and accurate diagnosis is often challenging. Positron emission tomography–computed tomography (PET-CT) and pathological biopsy can assist in the diagnostic process.Case descriptionA 52-year-old woman with acquired immune deficiency syndrome (AIDS) and a one-year history of chronic hepatitis B was admitted to the Infection Department of Chongqing Public Medical Center in September 2021. She had been on long-term antiviral therapy with Lamivudine, Tenofovir, and Efavirenz (3TC/TDF/EFV). Her chief complaints included a left groin mass, fever, and significant weight loss. Surgical excision and pathological examination of the left inguinal lymph nodes confirmed the diagnosis of IVLBCL. Following effective antiretroviral therapy and six cycles of CHOP/R-CHOP chemotherapy, the patient achieved complete remission. The patient remained free of lymphoma recurrence during the two-year follow-up; passed away due to COVID-19 in March 2023.ConclusionThis case illustrates four critical teaching points: (1) intravascular large B-cell lymphoma (IVLBCL) is a rare subtype of DLBCL; (2) isolated lymph node involvement is exceptionally uncommon in reported cases; (3) the absence of typical cutaneous or central nervous system involvement further complicates the diagnosis; and (4) its occurrence in an HIV-positive patient represents a particularly unusual clinical scenario. Early recognition of these atypical features, together with prompt combined antiretroviral and chemotherapy, achieved complete remission despite profound immunosuppression, highlighting the need for vigilant and individualized management in such rare and diagnostically challenging presentations.